Can Online Exercise Using Wearable Devices Improve Perceived Well-Being? A Study Among Patients with Coronary Artery Disease - Apostolia Ntovoli; Alexandros Mitropoulos; Maria Anifanti; Georgia Koukouvou; Evangelia Kouidi; Kostas Alexandris (Sensors)
Today, cardiovascular diseases contribute to approximately 17.9 million deaths annually worldwide. With reference to Europe, coronary artery disease (CAD) causes about 3.9 million deaths annually. Considering the positive physical and psychological outcomes of on-site exercise for CAD patients, this study aimed to expand the literature by examining the effects of a 6-month online exercise training program using wearable devices on CAD patients’ perceived well-being, measured with the PERMA profiler. Individual well-being is considered today as an important prerequisite for healthy societies. Thirty patients with a recent myocardial infarction (i.e., <4 weeks) were randomly assigned to either the online home-based or the community-based exercise group. Both groups followed the same 24-week exercise-based cardiac rehabilitation program three times per week. Each session consisted of a 30-min aerobic, followed by a 15-min strength workout, and then a 15-min balance and flexibility training. The results of the Mann–Whitney U tests and the z scores indicated that the Meaning of Life, Health, Accomplishment, Engagement, and Positive Relationship dimensions of the PERMA were statistically improved, and Negative Emotions were decreased. These findings support the importance of cardiac telerehabilitation for patients’ psychological health, demonstrating that online exercise using wearable devices can be a meaningful alternative to on-site exercise for patients with recent myocardial infarction. These results have policy implications as they provide arguments for providing online exercise for CAD patients as an alternative means for improving their psychological health.